Students’ psychological preparedness for inclusive education: an insight from special and inclusive education teachers - Manimaran, A; Badzis, Mastura (Research and Scientific Innovation Society (RSIS International), 2025)
The aim of inclusive education is to ensure that every child has equal rights to learning opportunities in mainstream classrooms regardless of ability or disability, physically or psychologically. The physical aspects of disability have been given much importance. However, special educational needs (SEN) students' inclusion depends not only on physical and institutional readiness but also on psychological preparedness. This study investigated the psychological preparedness of SEN students for inclusion in Malaysian national primary schools. The composition of this study represents the urban context, as it was carried out in schools around Klang Valley. By using a quantitative method, the research examined cognitive, social-cognitive, information-processing, and emotional aspects of students’ preparedness. These aspects are derived from the theoretical assumptions of Piaget, Vygotsky, Goleman, and the Information